Development of Penjasor Management Learning Media Based on Smart Learning System Assisted MIT APP Thunkable in Merdeka Belajar Era – Kampus Merdeka - Andika Prabowo; Bogy Restu Ilahi; Syafrial; Ari Sutisyana; Arwin; Andes Permadi; Defliyanto Defliyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to develop a Learning Media for Penjasor Management Based on a Smart Learning System Assisted by Mit App Thunkable to Improve Students' Critical Thinking. The Mit App Thunkable learning media based on Smart Learning, which was developed with the help of the Thunkable application, will be tested on odd semester students taking the Physical Education Study Program, FKIP UNIB. This study uses the Research and Development (R&D) method by collecting research data using a questionnaire based on the Likert scale. There are three questionnaires that will be distributed in this study, namely a material expert questionnaire, a media expert validation questionnaire, and a user response questionnaire. The purpose of distributing the questionnaire was to determine the feasibility of developing the Thunkable Mit App Assisted Penjasor Management media that the researchers made. As a result, the total score obtained from the combined validation of material experts, media, and users is 139.5 or an average score of 4.1 which means that the Mit App Thunkable-Assisted Penjasor Management Learning Media that the researcher developed is in the category suitable for use in Learning Activities.